Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fped.2022.828615
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Intervention for Children With Unilateral Renal Tumors to Reduce Toxicity

Abstract: Childhood renal tumors account for around 6% of all childhood cancers and 90% of these cases are Wilms tumor. In Europe, the SIOP-RTSG approach is considered standard of care and has resulted in five-year survival rates of over 90%. Efforts to decrease toxicity are now being pursued. Short-term fasting (STF), a short but strong reduction in calorie-intake, is associated with improved fitness, enhanced coping with acute physical stress and a lower risk of age-associated diseases. STF temporarily reduces growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…This was not as expected, given that on average, women tend to crave sweet treats more than men 37 38. Lastly, study personnel were found to significantly rate lower, influenced by their involvement in the active trials,29–31 possibly setting higher standards for the coordinating investigator or they were just sad to see a familiar batch of brownies distributed to others. The consistent findings in the subscores support the absence of the ‘Brownie-Effect’.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This was not as expected, given that on average, women tend to crave sweet treats more than men 37 38. Lastly, study personnel were found to significantly rate lower, influenced by their involvement in the active trials,29–31 possibly setting higher standards for the coordinating investigator or they were just sad to see a familiar batch of brownies distributed to others. The consistent findings in the subscores support the absence of the ‘Brownie-Effect’.…”
Section: Discussionmentioning
confidence: 89%
“…We selected 200 email addresses of healthcare professionals from departments associated with the active clinical trials 29–31. The survey was sent twice, on 26 April 2023 and 10 May 2023, and people were given a response window of 6 weeks from 26 April 2023.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary results indicate that brownies did not influence their views—but many saw value in short term fasting to improve wellbeing. While we complete the analysis and interpretation of our findings, we offer (in the spirit of open science) the potential intervention for BMJ readers to implement: a tried-and-tested brownie recipe meticulously honed by the coordinating investigator (box) 1011…”
mentioning
confidence: 99%